2012
DOI: 10.2308/iace-50148
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Students' Metacognition: The Association of Performance, Calibration Error, and Mindset

Abstract: In recognition of the evolving body of knowledge in the accounting profession, the American Institute of Certified Public Accountants (AICPA 2010) highlights the importance of viewing learning as a lifelong process that requires self-awareness and extends beyond the academic setting. Metacognition, the assessment and regulation of one's own learning, is a crucial element in lifelong learning. We draw upon judgment of learning research and introduce mindset theory to explore the relationship among (1) exam perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 43 publications
1
19
0
4
Order By: Relevance
“…In a study closely related to present work, the relationship between mindset and exam performance was investigated for students enrolled in an accounting course [9]. It was found that the majority of the students (72%) held growth mindsets and there was a mild association between the students' mindset scores and exam scores.…”
Section: Related Workmentioning
confidence: 85%
See 1 more Smart Citation
“…In a study closely related to present work, the relationship between mindset and exam performance was investigated for students enrolled in an accounting course [9]. It was found that the majority of the students (72%) held growth mindsets and there was a mild association between the students' mindset scores and exam scores.…”
Section: Related Workmentioning
confidence: 85%
“…We used the method of Ravenscroft et al [9] to compute the mindset score. We reversed the scores for the fixed-mindset questions, summed up the scores of the eight questions and divided the total by the number of questions, eight.…”
Section: B Context Of the Studymentioning
confidence: 99%
“…The use of teaching styles, such as the reciprocal and the self-check styles ( Mosston & Ashworth, 2002 ), can also help students to improve performance and to increase their awareness regarding their performance and the standards to judge their own and their peers’ performance in sport tasks ( Kolovelonis, Goudas, & Gerodimos, 2011 ). Moreover, considering that changing students’ mindsets can enhanced their achievement and decreased their calibration error ( Dweck, 2017 ; Ravenscroft et al, 2012 ) students should be taught that personal competencies and intelligence are malleable rather than fixed.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions focusing on promoting a growth mindset were beneficial for poorly performing students ( Paunesku et al, 2015 ). Moreover, it was found that a growth mindset was associated with improved performance and decreased calibration error ( Ravenscroft, Waymire, & West, 2012 ). Thus, promoting a growth mindset may help students to improve performance and decrease calibration error ( Dweck, 2017 ) contributing to the reversal of the underachievement among students ( Wong, 2016 ).…”
Section: Estimating Peers’ Performance: Am I Better or Worse Than Avementioning
confidence: 99%
“…The thoughts and attitudes with which accounting students approach academic tasks have been shown to influence their behaviors and task-related outcomes (Backof, Bamber, and Carpenter, 2016;Bloch, Brewer, and Stout, 2012;Ravenscroft, Waymire, and West, 2012). Some of these thoughts and attitudes, such as their ranging beliefs about the fixed or malleable nature of intelligence (Dweck, 2006), are developed and reinforced over long periods.…”
Section: Effects On Planningmentioning
confidence: 99%